Stuck in the past with push-pins on paper maps: Challenges of transition from manual to computerized crime mapping and analysis in Kenya - Baraka, Gachie Eliud (International journal of police science & management, 2019)
Although crimes and the modus operandi of perpetrators across the world change constantly, some policing tools, especially in developing countries, remain the same. This study sought to assess Kenyan police officers’ satisfaction with the use of paper maps and push-pins (manual tools) in crime analysis, and identify challenges to the adoption of computerized tools such as geographical information systems (GIS) at a time when most operations are driven by technology. A descriptive survey targeting 120 Kenyan police officers was carried out at the National Police Service (NPS) headquarters in Nairobi, but only 94 (78.3%) officers responded. The study reveals that 42.3% of respondents found manual tools to be useful in crime mapping and spatial analysis, whereas 67.8% felt that they were easy to use. The study indicates that 55.0% of respondents were satisfied with manual crime mapping and spatial analysis, mainly because it was easy to use. The study also identifies several challenges to the adoption of GIS in crime analysis. The study concludes that majority of respondents found manual crime-mapping tools to be easy to use, but less useful although still usable in the absence of alternatives. The NPS should consider implementing pilot projects of computerized crime mapping and spatial analysis to allow stakeholders to assess police operations against multiple platforms.